Notas sobre o gênero Leptopyrgota Hendel, com descrição de vinte e uma novas espécies do Brasil (Diptera, Pyrgotidae) - Bernardi, Nelson [UNESP] (Sociedade Brasileira de Zoologia, 1990)
Notes and comments on the Neotropical genus Leptopyrgota Hendel are presented. The following Brazilian species are described as new: apposita, celeriuscula, accolens, quaerens, ensifera, definienda, cocta, andrei, marci, sarae, juniae, liae, isabelae, gracilenta, flavipes, lenkoi, brevipennis, tibialis, minensis, caelifera, hesterna.